2022
DOI: 10.1021/acs.accounts.1c00635
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Nanotherapeutics Based on the Five Features Principle for Potent Elimination of Cancer Stem Cells

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Cancer stem cells (CSCs), also known as tumor initiating cells or tumor repopulating cells, which comprise only a small fraction of tumor, have received tremendous attention during the past two decades, as they are considered as the ringleader for initiation and progression of tumors, therapy resistance, metastasis, and recurrence in the clinic. Hence, eradicating CSCs is critical for successful cancer treatment. To that end, various CSC-targeting therapeutic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…This may be the result of the enhanced permeability and retention effect (EPR effect) and the relatively long circulation of Ce6@HMPB NPs than free Ce6 in blood. 67–70 The above results demonstrated that Ce6@HMPB NPs efficiently accumulated and lingered in tumor tissues, which would benefit the following in vivo phototherapy.…”
Section: Resultsmentioning
confidence: 75%
“…This may be the result of the enhanced permeability and retention effect (EPR effect) and the relatively long circulation of Ce6@HMPB NPs than free Ce6 in blood. 67–70 The above results demonstrated that Ce6@HMPB NPs efficiently accumulated and lingered in tumor tissues, which would benefit the following in vivo phototherapy.…”
Section: Resultsmentioning
confidence: 75%
“…Therefore, it is pivotal to understand the initiation of metastasis. CSCs have been reported to initiate tumor metastasis ( Zhang et al, 2022 ). The stem cell biomarker CD44 and pluripotent transcription factors NANOG, MYC, and OCT4 have now been validated to contribute to the maintenance of CSCs and are widely used to identify CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) are characterized in many cancers and contribute to tumorigenesis, recurrence, and metastatic spread ( Zhang et al, 2022 ). In RCC, cell populations with stem-like properties have been isolated, and CSCs are highly enriched in tumors with high pathological stage, venous and lymphatic invasion, and distant metastases ( Varna et al, 2015 ; Fendler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…46 Therefore, nanoMedicine plays an important role in tumor therapy. 47 The particle size, shape, arrangement, surface charge distribution, and surface chemistry of nanomedicine carriers are the key factors that determine their physicochemical properties and interactions with the biological environment (molecules, cells, tissues, etc.). 48,49 The first generation of nanoMedicines was based on the enhanced permeability and retention (EPR) effect of the tumor vasculature to load traditional small-molecule antitumor drugs with liposomes as carriers to achieve drug enrichment in tumors.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…However, polymeric nanoparticles have the potential risk of increased toxicity and particle aggregation, so polymers with high biocompatibility and degradability, such as poly (lactic acid) (PLA), poly (lactic acid-hydroxyacetic acid) (PLGA), and polycaprolactone (PCL), are being developed. [45][46][47]…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%